GRANDPARENTS’ CHILDCARE SUPPORT IN LITHUANIA: PREDICTORS AND CONSEQUENCES FOR WELL-BEING - Kraniauskienė, Sigita; Gedvilaitė-Kordušienė, Margarita (Sociologija. Mintis ir veiksmas, 2012)
Using theories of intergenerational solidarity and conflict, and data from the Demographic Research Institute’s 2009 survey, ‘Gender and Generations’, this article analyses childcare support provided by grandparents in Lithuania. The survey results revealed that the most active grandparents are aged between 50 and 65, and that half of those grandparents participating in childcare also have a job. The most important factors determining grandparents’ participation in childcare are gender, marital status, subjective health and whether grandparents and grandchildren live together or separately. To assess the connection between grandparents’ well-being and their role in childcare, the Demographic Research Institute’s well-being index, linked to demographic processes, was employed. The results show that childcare provision is related only to some aspects of grandparents’ well-being; this article discusses the distribution of various aspects of wellbeing by the provision or non-provision of childcare and by other crucial predictors: the age, gender and employment status of grandparents.Key words: grandparents, child care, well-being, multiple roles.